Study of triethanolamine on regulating early strength of fly ash-based chemically foamed geopolymer. (December 2022) - Feng, Weipeng; Jin, Yu; Zheng, Dapeng; Fang, Yuan; Dong, Zhijun; Cui, Hongzhi
Abstract: This study investigates the role of triethanolamine (TEA) in regulating the early strength of ultra-lightweight (∼460 kg/cm 3 ) fly ash-based chemically foamed geopolymer. The reaction kinetics, pore distribution and skeleton strength were examined using isothermal calorimetry, X-ray microtomography, and solid-state nuclear magnetic resonance spectroscopy, respectively. The three-dimensional pore spatial distribution patterns were statistically assessed by applying the Nearest-neighbor distance-based techniques. The results showed that TEA can regulate the early strength of geopolymer foam by rendering homogeneous pore sizes and spatial distributions even when the geopolymerization of the skeleton is retarded. Furthermore, 0.3 % TEA reduced the compressive strength of the skeleton by 13.4 %, from 105.8 MPa to 91.6 MPa, but doubled the specific strength of the geopolymer foam from 2271 N·m/kg to 4662 N·m/kg. The proposed mechanism suggests that foaming kinetics can be regulated for a homogeneous pore distribution by manipulating the complexing effect. Highlights: Pore spatial pattern was assessed by Nearest-neighbor distance-based techniques. Mechanism of TEA on the skeletal development of geopolymer foam was proposed. TEA retarded geopolymerization by complexing with Al 3+ from fly ash. TEA accelerated fly ash dissolution to hinder catalyzed decomposition of H2 O2 .